A study of Corporate Entrepreneurship at ITI LifeSciences - Middleton, Barry (2007)
ITI Life Sciences is a private organisation based in Dundee, Scotland, which was set up in 2003 through Scottish Enterprise (SE), the publicly funded Scottish regional development agency. ITI Life Sciences has grown from a start up phase into a more mature phase of growth, yet the organization has been grappling with a range of corporate issues. It has long been held that in general, entrepreneurial firms display more innovative, risk taking and proactive behaviour than other firms thanks in part to the strategic perspective shared in the organisation. It is therefore timely to look at ITI Life Sciences through the lens of corporate entrepreneurship and through the use of some models and key concepts, help identify critical CE focussed issues for ITI Life Sciences going forward. Through a customised Entrepreneurial Health Audit of the whole organisation and application of the Herman thinking styles concepts linked to the creative problem solving model, a range of issues relating to CE at ITI Life sciences were highlighted. The Entrepreneurial Health Audit results reflect the multidimensional complexity of CE in an organisation. ITI Life Sciences appeared to display a weak level of entrepreneurial intensity which had been the result of a lack of management support for CE, incentivisation around innovation and a general company mindset which has shifted from originally being considered very entrepreneurial to becoming much more conservative and innovation/risk averse. However, the analysis revealed a considerable level of CE potential which if addressed, may lead the organisation to develop a higher level of entrepreneurial intensity. The Hermann thinking styles analysis provided insight into the thinking styles of each functional team at ITI Life Sciences and highlighted some differences between two key teams in particular which have had communication and collaborative difficulties in the past. An appreciation of these differences should lead to a more harmonious working relationship going forward which could bolster entrepreneurial intensity. The high level of CE potential is reinforced by the comparing the main ITI operating process with the creative problem solving model. Through this, the different stages of the creative problem solving model are represented in the ITI process map with strong affinity, not just for the processes, but for the different mindsets and abilities required at each stage. This study has shown that by following a frame work such as the Entrepreneurial Health Audit combined with the Hermann thinking styles concepts and a creative problem solving model, it is possible to gather a considerable amount of information on an organisation and relate this information to CE. This information has catalysed the creation of a strategy for addressing CE at ITI Life Sciences which may result in developing the CE potential in the organisation.